Saturation and hysteresis effects in ionospheric modification experiments observed by the CUTLASS and EISCAT radars - D. M. Wright; J. A. Davies; T. K. Yeoman; T. R. Robinson; H. Shergill (Annales Geophysicae, 2006)
The results of high latitude ionospheric modification experiments utilising the EISCAT heating facility at Tromsø are presented. As a result of the interaction between the high power pump waves and upper hybrid waves in the ionosphere, field-aligned electron density irregularities are artificially excited. Observations of these structures with the CUTLASS coherent HF radars and the EISCAT incoherent UHF radar exhibit hysteresis effects as the heater output power is varied. These are explained in terms of the two-stage mechanism which leads to the growth of the irregularities. Experiments which involve preconditioning of the ionosphere also indicate that hysteresis could be exploited to maximise the intensity of the field-aligned irregularities, especially where the available heater power is limited. In addition, the saturation of the irregularity amplitude is considered. Although, the rate of irregularity growth becomes less rapid at high heater powers it does not seem to fully saturate, indicating that the amplification would continue beyond the capabilities of the Tromsø heater - currently the most powerful of its kind. It is shown that the CUTLASS radars are sensitive to irregularities produced by very low heater powers (effective radiated powers <4 MW). This fact is discussed from the perspective of a new heating facility, SPEAR, located on Spitzbergen and capable of transmitting high frequency radio waves with an effective radiated power ~10% of that of the Tromsø heater (28MW).